Plant Growth Modeling Using L-System Approach and Its Visualization - Suyantohadi, Atris; Alfiyan, Alfiyan; Hariadi, Mochamad; Purnomo, Mauridhi Hery (UI Scholars Hub, 2010)
The visualization of plant growth modeling using computer simulation has rarely been conducted with Lindenmayer System (L-System) approach. L-System generally has been used as framework for improving and designing realistic modeling on plant growth. It is one kind of tools for representing plant growth based on grammar sintax and mathematic formulation. This research aimed to design modeling and visualizing plant growth structure generated using L-System. The environment on modeling design used three dimension graphic on standart OpenGL format. The visualization on system design has been developed by some of L-System grammar, and the output graphic on three dimension reflected on plant growth as a virtual plant growth system. Using some of samples on grammar L-System rules for describing of the charaterictics of plant growth, the visualization of structure on plant growth has been resulted and demonstrated.